Effect Of Career Development, Work Motivation And Competence Of Employee Performance Office PT. Adzkia Masa Depan Medan - Annisya Risky Siagian; Adelina Lubis; Audia Junita (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2024)
In a company, the primary resource is its human resources, often referred to as employees. Human resources play a crucial role at all levels, from lower management to top management, in ensuring that the company achieves its objectives. For this reason, employees are required to demonstrate strong performance, which is influenced by several key factors, including career development, motivation, and competence. These factors not only shape how employees contribute to organizational success but also determine their individual growth and satisfaction. This study investigates the impact of career development, work motivation, and competence on employee performance. A quantitative research approach was employed, with data collected through the distribution of questionnaires and library research. The study sample consisted of 32 employees at PT. Adzkia Masa Depan Medan, selected using the Saturated Sample method. This method ensures that all members of the population are included in the study, allowing for comprehensive data collection. Data analysis was conducted using multiple linear regression analysis in SPSS 20 software. This technique enables researchers to assess the relationship and impact of career development, work motivation, and competence on employee performance. Furthermore, hypothesis testing was conducted to determine the significance of these variables on performance outcomes. The findings of this study provide valuable insights into the critical factors that influence employee productivity and effectiveness, highlighting the importance of fostering career growth opportunities, maintaining high levels of motivation, and enhancing employee competencies. These insights are expected to contribute to improved HR practices and strategic decision-making in organizational contexts.